Assessing the validity of digital health literacy instrument for secondary school students in Ghana: The polychoric factor analytic approach - Agormedah, Edmond Kwesi; Quansah, Frank; Ankomah, Francis; Hagan, John Elvis; Srem-Sai, Medina; Abieraba, Richard Samuel Kwadwo; Frimpong, James Boadu; Schack, Thomas (Frontiers in Digital Health, 2022)
The emergence of the coronavirus pandemic resulted in the heightened need for digital health literacy among the youth of school-going age. Despite the relevance of digital health literacy among the general public (including students), it appears the measurement of digital health literacy is still a challenge among researchers. Recently, Dadackinski and colleagues adapted existing digital health literacy instrument measures to fit the COVDID-19 specific situation. Since this development, the instrument has been widely used with few validation studies with none in Africa and specifically, in Ghana. The purpose of the study was to assess the validity of the digital health literacy instrument for secondary school students in Ghana, using the polychoric factor analysis. About 1,392 secondary school students were sampled from schools in Ghana. The digital health literacy instrument was administered to the respondents, thereof. The latent structure of the DHLI was four. Further, sufficient validity evidence was found regarding the construct validity of the DHLI. The findings from the study support the validity of the DHLI and consequently, its utility within the Ghanaian context. With the growing need for digital health literacy among younger people globally, the DHLI provides sufficient grounds for scaling them based on their level of literacy. There is a need for the instrument to be adapted and re-validated in Ghana and among the different population to widen its reproducibility.